Profile composition of knowledge dimension in learning activities during the Covid-19 pandemic in structure and function of plant - Eriska Novita Sari; Bambang Subali (JPBI (Jurnal Pendidikan Biologi Indonesia), 2021)
The covid-19 pandemic has an impact on the biology learning process in achieving learning objectives. This study aimed to describe the profile of the 4-dimensional composition of knowledge in the Biology learning process during the Covid-19 pandemic on the topic of the structure and function of junior high school plant tissues based on the 2013 Graduate Competency Standards curriculum. This study uses a qualitative research method with a descriptive approach. The population of this study was teachers and students of Junior High School Al Ma'ruf Kudus. The sample of this study was taken using a purposive sampling technique. Collecting data using document observation of learning tools, interviews, and documentation of evaluation of learning outcomes. Data analysis using an interactive model. The results of this study describe the composition of the types of knowledge dimensions in learning the structure and function of plant tissues which include factual, conceptual, procedural, and metacognitive knowledge, with some of the different learning activities based on the characteristics, methods, and learning models in each sub-material discussion. Further research can be conducted to find out how to fulfill the knowledge dimension in biology learning materials carried out during the pandemic.